Dopamine D1/D5 Receptor Signaling Is Involved in Arrhythmogenesis in the Setting of Takotsubo Cardiomyopathy - Huang, Mengying; Yang, Zhen; Li, Yingrui; Lan, Huan; Cyganek, Lukas; Yuecel, Goekhan; Lang, Siegfried; Bieback, Karen; El-Battrawy, Ibrahim; Zhou, Xiaobo; Borggrefe, Martin; Akin, Ibrahim (Frontiers in Cardiovascular Medicine, 2022)
Background: Previous studies suggested involvement of non-ß-adrenoceptors in the pathogenesis of Takotsubo cardiomyopathy (TTC). This study was designed to explore possible roles and underlying mechanisms of dopamine D1/D5 receptor coupled signaling in arrhythmogenesis of TTC. Methods: Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) were challenged by toxic concentration of epinephrine (Epi, 0.5 mM for 1h) for mimicking the catecholamine excess in setting of TTC. Specific receptor blockers and activators were used to unveil roles of D1/D5 receptors. Patch clamp, qPCR and FACS analyses were performed in the study. Results: High concentration Epi and two dopamine D1/D5 receptor agonists ((±)-SKF 38393 and fenoldopam) reduced the depolarization velocity and prolonged the duration of action potentials (APs) and caused arrhythmic events in iPSC-CMs, suggesting involvement of dopamine D1/D5 receptor signaling in arrhythmogenesis associated with QT interval prolongation in the setting of TTC. (±)-SKF 38393 and fenoldopam enhanced the reactive oxygen species (ROS)-production. H2O2 (100 µM) recapitulated the effects of (±)-SKF 38393 and fenoldopam on APs and a ROS-blocker N-acetylcysteine (NAC, 1 mM) abolished the effects, suggesting that the ROS-signaling is involved in the dopamine D1/D5 receptor actions. A NADPH oxidases blocker and a PKA- or PKC-blocker suppressed the effects of the dopamine receptor agonist, implying that PKA, NADPH oxidases and PKC participated in dopamine D1/D5 receptor signaling. The abnormal APs resulted from dopamine D1/D5 receptor activation-induced dysfunctions of ion channels including the Na+ and L-type Ca2+ and IKr channels. Conclusions: Dopamine D1/D5 receptor signaling plays important roles for arrhythmogenesis of TTC. Dopamine D1/D5 receptor signaling in cardiomyocytes might be a potential target for treating arrhythmias in patients with TTC.